The Influence of Rheological Properties on The Pump Power Requirement for Transfering Ketchup - Darwin Darwin (Rona Teknik Pertanian, 2021)
Abstract. This research aimed to analyze the influence of rheological properties of ketchup on the pump power, required during transporting process. This research was done through using a computer programme designed for calculating and analyzing the influence of rheological properties toward materials and equipments installed in the transport system. Those rheological properties derived from laboratory analysis and literature review include viscosity and density from any type of ketchup. Results analysed by a computer programming revealed that flow behaviour Index (n) and consistency coefficient (m) were the rheological properties interacting with each other since these parameters were the viscosity of ketchup that influences energy losses in the transport system. Once the total of energy losses was obtained from the system, the pump power required for transfering the product also can be known. Based on the simulation conducted by using rheological parameters of ketchup with consistency coefficient of 12.33 PaSn, and flow behaviour Index at 0.41 was obtained total energy losses at 202.26 J/kg with the pump power requirement at 0.22 kW. Once consistency coefficient was 18.7 PaSn, and flow behaviour Index was at around 0.4, the total of energy losses increased to 277.58 J/kg with pump power requirement at 0.28 kW.